Seroprevalence study of brucellosis in wild boar hunted for private consumption in northeast Portugal - Ruano, Zita Martins (2024)
Brucellosis is an important infectious disease caused by bacteria of the genus Brucella. In the northeast region of Portugal, infection with Brucella melitensis is endemic in small ruminants, and there are also humans’ cases. However, the epidemiological role of the wild boar in the dynamics of this disease in this region is unknown. In this study, a total of 332 blood samples were collected from wild boar hunted in thirty-six hunting areas during the 2022/2023 hunting season. All were taken by the hunters for private consumption, with no evisceration or examination in the feld. Serum samples were tested by indirect ELISA (i-ELISA). It was observed that 88 wild boars were exposed to Brucella spp., pointing to a seroprevalence of 26.5% (95% CI: 21.8 – 31.3%). This high prevalence underlines the importance that wild boar may have in the dynamics of this disease in the region and its potential transmission to other animals, and to humans (for example, during the handling of carcasses). Increased awareness and knowledge of brucellosis in wild boar is essential for the implementation of efective practices and habits and, consequently, for the control and prevention of this important zoonosis.